Cascaded parametric amplification based on spatiotemporal modulations - Yang, Qianru (2023)
Active devices have drawn considerable attention owing to their powerful capabilities to manipulate electromagnetic waves. Fast and periodic modulation of material properties is one of the key obstacles to the practical implementation of active metamaterials and metasurfaces. In this study, to circumvent this limitation, we employ a cascaded phase-matching mechanism to amplify signals through spatiotemporal modulation of permittivity. Our results show that the energy of the amplified fundamental mode can be efficiently transferred to that of the high harmonic components if the spatiotemporal modulation travels at the same speed as the signals. This outstanding benefit enables a low-frequency pump to excite parametric amplification. The realization of cascaded parametric amplification is demonstrated by finite-difference time-domain (FDTD) simulations and analytical calculations based on the Bloch–Floquet theory. We find that the same lasing state can always be excited by an incidence at different harmonic frequencies. The spectral and temporal responses of the space-time modulated slab strongly depend on the modulation length, modulation strength, and modulation velocity. Furthermore, the cascaded parametric oscillators composed of a cavity formed by photonic crystals are presented. The lasing threshold is significantly reduced by the cavity resonance. Finally, the excitation of cascaded parametric amplification relying on the Si-waveguide platform is demonstrated. We believed that the proposed mechanism provides a promising opportunity for the practical implementation of intense amplification and coherent radiation based on active metamaterials.